FAKTOR – FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK (Studi pada Wajib Pajak Orang Pribadi yang Terdaftar di KPP Pratama Semarang Timur) - Chintya Ruri Ayuningtyas, 12.05.52.0013; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2019)
This study aims to examine and analyze empirically the effects of tax socialization, the application of the e-SPT system, tax sanction education level, and motivation towards taxpayer compliance with registered individual taxpayers at the Pratama Semarang East Tax Office in 2014 - 2017. The population used in this study is an individual taxpayer registered at the Pratama East Semarang Tax Office as many as 34,428 WPOP in 2017. The sampling technique in this study was purposive sampling, namely sampling based on criteria. The criteria used are taxpayers aged = ≥ 20 years to ≤ 64 years with self-employment and are in the environment of the East Semarang Pratama Tax Office. The data analysis technique uses multiple linear regression analysis. The results showed that tax socialization had a positive effect on tax compliance. The implementation of the e-SPT system has a positive effect on taxpayer compliance. Education level has a positive effect on tax compliance. Tax sanctions have a positive effect on tax compliance. Motivation has a positive effect on tax complianceKeywords: tax socialization, implementation of e-SPT system, tax sanction education level, motivation and tax compliance